Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Alignment between Duplex Sequencing and transgenic rodent mutation assay data in the assessment of in vivo NDMA-induced mutagenesis - Anne L. Ashford; Daniela Nachmanson; John W. Wills; Jacob E. Higgins; Thomas H. Smith; Kevin C. Vavra; Farah A. Dahalan; Jonathan Howe; Joanne M. Elloway; Jesse J. Salk; Ann Doherty; Anthony M. Lynch (Archives of Toxicology, 2025)

Killer Whale ( Orcinus orca ) Opportunistic Predation Events on Whale Sharks ( Rhincodon typus ) in the Eastern Tropical Pacific - Hernán Orellana‐Vásquez; Galo Echeverría; Jacob Moscoso; Santiago Díaz‐Pazmiño; Daniela Alarcón‐Ruales (Marine Mammal Science, 2025)

Ultra-fast metamorphic reaction during regional metamorphism - Jia-Hui Liu; Pierre Lanari; Renée Tamblyn; Hugo Dominguez; Jörg Hermann; Daniela Rubatto; Jacob B. Forshaw; Francesca Piccoli; Qian W.L. Zhang; Thorsten A. Markmann; Julien Reynes; Zhen M.G. Li; et al. (Geochimica et Cosmochimica Acta, 2025)

Navigating trade-offs in design for sustainability and circularity: A tool for decision making leveraging narratives and multiple criteria decision analysis - Giácomo Parolin; Jacob Arnbjerg; Tim C. McAloone; Daniela C.A. Pigosso (Journal of Cleaner Production, 2025)

Enabling environmental sustainability and circularity assessment in technology development: The Value-Impact Scanner - Giácomo Parolin; Jacob Arnbjerg; Henriette A. Eriksen; Tim C. McAloone; Daniela C.A. Pigosso (Sustainable Production and Consumption, 2024)

Editorial Introduction to the Topical Collection: Accrual of Climate Change Risk in Six Vulnerable Countries - Daniela Jacob; Tania Guillén Bolaños (Climatic Change, 2024)

Genetic selection for reduced parasite load in Atlantic salmon: Zero-sum game or a tool for group-level protection against sea lice? - Jørgen Ødegård; Matias Medina; Jacob S. Torgersen; Sven A. Korsvoll; Robert Deerenberg; José M. Yáñez; Daniela Cichero; Paulina Lopez; Thomas Moen; Sissel Kjøglum (Aquaculture, 2024)

An assessment tool to improve rural groundwater access: Integrating hydrogeological modelling with socio-technical factors - Daniela Cid-Escobar; Albert Folch; Nuria Ferrer; Jacob Katuva; Xavier Sanchez-Vila (Science of The Total Environment, 2024)

Future climate change in the Northern Indian Ocean as simulated with a high-resolution regional earth system model - Dmitry V. Sein; Stanislav D. Martyanov; Anton Y. Dvornikov; William Cabos; Vladimir A. Ryabchenko; Alok K. Mishra; Natalia Limareva; Evgenia Alekseeva; Daniela Jacob; Pankaj Kumar (Climate Dynamics, 2024)
This study examines the future climate change in the South Asia region during 2070–2099 with respect to the historical period (1975–2004) under RCP8.5 scenario using a high-resolution regional earth system model. We found substantial changes in the key climatic parameters over the South Asia region including ocean biological productivity, however, the magnitude of response varies spatially. A substantial increase (> 2.5 °C) in the projected annual-mean sea surface temperature (SST) was found over the Indian Ocean with the highest increase (~ 3.4 °C) locally in the northern part of the Arabian Sea and in the Persian Gulf, SST changes being significant throughout the study area with 95% confidence level. The changes in the sea surface salinity showed strong spatial variability with the highest freshening over northern Bay of Bengal and highest salinity in the Persian Gulf followed by northern Arabian Sea. The amount of annual-mean precipitation will substantially increase over the eastern coast of the Bay of Bengal (up to 1.5–2.0 mm/day) and along the equator in the band 10° S–10° N (0.5–1.5 mm/day), while it will decrease over the western part of the Bay of Bengal and in the northern states of India (− 0.5 to 1.0 mm/day). The most pronounced increase of precipitation rate in the future climate will occur over India (3–5 mm/day) and the eastern coasts of the Bay of Bengal (> 5 mm/day) during the monsoon period, and over the equatorial band (2–3 mm/day) during the post-monsoon period, with all precipitation changes indicated above being significant at 95% confidence level.

Adopting duplex sequencing technology for genetic toxicity testing: A proof-of-concept mutagenesis experiment with N-ethyl-N-nitrosourea (ENU)-exposed rats - Stephanie L. Smith-Roe; Cheryl A. Hobbs; Victoria Hull; J. Todd Auman; Leslie Recio; Michael A. Streicker; Miriam V. Rivas; Gabriel A. Pratt; Fang Yin Lo; Jacob E. Higgins; Elizabeth K. Schmidt; Lindsey N. Williams; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Benefits of simulating precipitation characteristics over Africa with a regionally-coupled atmosphere–ocean model - Torsten Weber; William Cabos; Dmitry V. Sein; Daniela Jacob (Climate Dynamics, 2023)
High-quality climate information at appropriate spatial and temporal resolution is essential to develop and provide tailored climate services for Africa. A common method to produce regional climate change data is to dynamically downscale global climate projections by means of regional climate models (RCMs). Deficiencies in the representation of the sea surface temperatures (SSTs) in earth system models (ESMs) and missing atmosphere–ocean interactions in RCMs contribute to the precipitation bias. This study analyzes the influence of the regional atmosphere–ocean coupling on simulated precipitation and its characteristics over Africa, and identifies those regions providing an added value using the regionally coupled atmosphere–ocean model ROM. For the analysis, the MPI-ESM-LR historical simulation and emission scenario RCP8.5 were dynamically downscaled with ROM at a spatial resolution of 0.22° × 0.22° for the whole African continent, including the tropical Atlantic and the Southwest Indian Ocean. The results show that reduced SST warm biases in both oceans lead to more realistic simulated precipitation over most coastal regions of Sub-Saharan Africa and over southern Africa to varying degrees depending on the season. In particular, the annual precipitation cycles over the coastal regions of the Atlantic Ocean are closer to observations. Moreover, total precipitation and extreme precipitation indices in the coupled historical simulation are significantly lower and more realistic compared to observations over the majority of the analyzed sub-regions. Finally, atmosphere–ocean coupling can amplify or attenuate climate change signals from precipitation indices or even change their sign in a regional climate projection.

Regional earth system model for CORDEX‐South Asia: A comparative assessment of RESM and ESM over the tropical Indian Ocean - Pankaj Kumar; Subrat Mallick; Alok Kumar Mishra; Aditya Kumar Dubey; Gaurav Tiwari; Dimitry V. Sein; William Cabos; Daniela Jacob (International Journal of Climatology, 2022)
Understanding climate variability requires good quality high resolution spatially and temporally varying ocean fields due to its decisive role in regulating the region's climate, including the Indian summer monsoon. In this regard, we employed a new high‐resolution regional earth system model (RESM), namely ROM over CORDEX South Asia. We demonstrated the performance of the RESM and its added value over the global earth system model, namely MPI‐ESM, in simulating the hydrographic characteristics and associated mechanism over the tropical Indian Ocean (TIO). ROM shows better skill than MPI‐ESM in simulating the near‐surface and subsurface characteristics of the ocean. However, larger added values are noticed for subsurface (>350 m) thermal structure. MPI‐ESM's cold sea surface temperature (SST) bias is reduced in ROM which is associated with weaker winds, anomalous cyclonic wind stress curl, enhanced stratifications, and a shallower mixed layer, resulting in greater upper‐ocean heating. The reduced SST bias is also consistent with improved ocean meridional heat transport (OMHT) in ROM. For example, reduced southward export of OMHT over the Arabian Sea increases the surface warming by ~4%, reducing the RMSE by ~0.2–0.6°C and becoming closer to observation. The anomalous cyclonic wind stress curl, in turn, caused mixed layer stratifications in the western Indian Ocean. The advective heat transfer from the south‐eastern Indian Ocean to the western Indian Ocean reduced oceanic cooling by vertical processes, overcame the cooling by the net loss of surface heat fluxes, and favoured the TIO's surface warming.

Regional earth system modelling framework for CORDEX-SA: an integrated model assessment for Indian summer monsoon rainfall - Pankaj Kumar; Alok Kumar Mishra; Aditya Kumar Dubey; Aaquib Javed; Md. Saquib Saharwardi; Amita Kumari; Disha Sachan; William Cabos; Daniela Jacob; Dmitry V. Sein (Climate Dynamics, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Global exposure of population and land‐use to meteorological droughts under different warming levels and SSPs : A CORDEX ‐based study - Jonathan Spinoni; Paulo Barbosa; Edoardo Bucchignani; John Cassano; Tereza Cavazos; Alessandro Cescatti; Jens H. Christensen; Ole B. Christensen; Erika Coppola; Jason P. Evans; Giovanni Forzieri; Beate Geyer; et al. (International Journal of Climatology, 2021)
Global warming is likely to cause a progressive drought increase in some regions, but how population and natural resources will be affected is still underexplored. This study focuses on global population, forests, croplands and pastures exposure to meteorological drought hazard in the 21st century, expressed as frequency and severity of drought events. As input, we use a large ensemble of climate simulations from the Coordinated Regional Climate Downscaling Experiment (CORDEX), population projections from the NASA‐SEDAC dataset and land‐use projections from the Land‐Use Harmonization 2 project for 1981–2100. The exposure to drought hazard is presented for five Shared Socioeconomic Pathways (SSP1‐SSP5) at four Global Warming Levels (GWLs: 1.5°C to 4°C). Results show that considering only Standardized Precipitation Index (SPI; based on precipitation), the SSP3 at GWL4 projects the largest fraction of the global population (14%) to experience an increase in drought frequency and severity (versus 1981–2010), with this value increasing to 60% if temperature is considered (indirectly included in the Standardized Precipitation‐Evapotranspiration Index, SPEI). With SPEI, considering the highest GWL for each SSP, 8 (for SSP2, SSP4, SSP5) and 11 (SSP3) billion people, that is, more than 90%, will be affected by at least one unprecedented drought. For SSP5 at GWL4, approximately 2 × 10 6 km 2 of forests and croplands (respectively, 6% and 11%) and 1.5 × 10 6 km 2 of pastures (19%) will be exposed to increased drought frequency and severity according to SPI, but for SPEI this extent will rise to 17 × 10 6 km 2 of forests (49%), 6 × 10 6 km 2 of pastures (78%) and 12 × 10 6 km 2 of croplands (67%), being mid‐latitudes the most affected. The projected likely increase of drought frequency and severity significantly increases population and land‐use exposure to drought, even at low GWLs, thus extensive mitigation and adaptation efforts are needed to avoid the most severe impacts of climate change.

Impact of air–sea coupling on the climate change signal over the Iberian Peninsula - Alba de la Vara; William Cabos; Dmitry V. Sein; Claas Teichmann; Daniela Jacob (Climate Dynamics, 2021)
In this work we use a regional atmosphere–ocean coupled model (RAOCM) and its stand-alone atmospheric component to gain insight into the impact of atmosphere–ocean coupling on the climate change signal over the Iberian Peninsula (IP). The IP climate is influenced by both the Atlantic Ocean and the Mediterranean sea. Complex interactions with the orography take place there and high-resolution models are required to realistically reproduce its current and future climate. We find that under the RCP8.5 scenario, the generalized 2-m air temperature (T2M) increase by the end of the twenty-first century (2070–2099) in the atmospheric-only simulation is tempered by the coupling. The impact of coupling is specially seen in summer, when the warming is stronger. Precipitation shows regionally-dependent changes in winter, whilst a drier climate is found in summer. The coupling generally reduces the magnitude of the changes. Differences in T2M and precipitation between the coupled and uncoupled simulations are caused by changes in the Atlantic large-scale circulation and in the Mediterranean Sea. Additionally, the differences in projected changes of T2M and precipitation with the RAOCM under the RCP8.5 and RCP4.5 scenarios are tackled. Results show that in winter and summer T2M increases less and precipitation changes are of a smaller magnitude with the RCP4.5. Whilst in summer changes present a similar regional distribution in both runs, in winter there are some differences in the NW of the IP due to differences in the North Atlantic circulation. The differences in the climate change signal from the RAOCM and the driving Global Coupled Model show that regionalization has an effect in terms of higher resolution over the land and ocean.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Editorial for the CORDEX-CORE Experiment I Special Issue - Filippo Giorgi; Erika Coppola; Claas Teichmann; Daniela Jacob (Climate Dynamics, 2021)

Climate hazard indices projections based on CORDEX-CORE, CMIP5 and CMIP6 ensemble - Erika Coppola; Francesca Raffaele; Filippo Giorgi; Graziano Giuliani; Gao Xuejie; James M. Ciarlo; Taleena Rae Sines; José Abraham Torres-Alavez; Sushant Das; Fabio di Sante; Emanuela Pichelli; Russell Glazer; et al. (Climate Dynamics, 2021)

Assessing mean climate change signals in the global CORDEX-CORE ensemble - Claas Teichmann; Daniela Jacob; Armelle Reca Remedio; Thomas Remke; Lars Buntemeyer; Peter Hoffmann; Arne Kriegsmann; Ludwig Lierhammer; Katharina Bülow; Torsten Weber; Kevin Sieck; Diana Rechid; et al. (Climate Dynamics, 2021)
The new Coordinated Output for Regional Evaluations (CORDEX-CORE) ensemble provides high-resolution, consistent regional climate change projections for the major inhabited areas of the world. It serves as a solid scientific basis for further research related to vulnerability, impact, adaptation and climate services in addition to existing CORDEX simulations. The aim of this study is to investigate and document the climate change information provided by the CORDEX-CORE simulation ensemble, as a part of the World Climate Research Programme (WCRP) CORDEX community. An overview of the annual and monthly mean climate change information in selected regions in different CORDEX domains is presented for temperature and precipitation, providing the foundation for detailed follow-up studies and applications. Initially, two regional climate models (RCMs), REMO and RegCM were used to downscale global climate model output. The driving simulations by AR5 global climate models (AR5-GCMs) were selected to cover the spread of high, medium, and low equilibrium climate sensitivity at a global scale. The CORDEX-CORE ensemble has doubled the spatial resolution compared to the previously existing CORDEX simulations in most of the regions (25 $$\,km$$ km (0.22 $$^{° }$$ ∘ ) versus 50 $$\,km$$ km (0.44 $$^{° }$$ ∘ )) leading to a potentially improved representation of, e.g., physical processes in the RCMs. The analysis focuses on changes in the IPCC physical climate reference regions. The results show a general reasonable representation of the spread of the temperature and precipitation climate change signals of the AR5-GCMs by the CORDEX-CORE simulations in the investigated regions in all CORDEX domains by mostly covering the AR5 interquartile range of climate change signals. The simulated CORDEX-CORE monthly climate change signals mostly follow the AR5-GCMs, although for specific regions they show a different change in the course of the year compared to the AR5-GCMs, especially for RCP8.5, which needs to be investigated further in region specific process studies.

A new spatially distributed added value index for regional climate models: the EURO-CORDEX and the CORDEX-CORE highest resolution ensembles - James M. Ciarlo`; Erika Coppola; Adriano Fantini; Filippo Giorgi; XueJie Gao; Yao Tong; Russell H. Glazer; Jose Abraham Torres Alavez; Taleena Sines; Emanuela Pichelli; Francesca Raffaele; Sushant Das; et al. (Climate Dynamics, 2021)

Seasonal temperature response over the Indochina Peninsula to a worst-case high-emission forcing: a study with the regionally coupled model ROM - Shoupeng Zhu; Fei Ge; Frank Sielmann; Mengting Pan; Klaus Fraedrich; Armelle Reca C. Remedio; Dmitry V. Sein; Daniela Jacob; Hao Wang; Xiefei Zhi (Theoretical and Applied Climatology, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Regional climate downscaling over Europe: perspectives from the EURO-CORDEX community - Daniela Jacob; Claas Teichmann; Stefan Sobolowski; Eleni Katragkou; Ivonne Anders; Michal Belda; Rasmus Benestad; Fredrik Boberg; Erasmo Buonomo; Rita M. Cardoso; Ana Casanueva; Ole B. Christensen; et al. (Regional Environmental Change, 2020)
The European CORDEX (EURO-CORDEX) initiative is a large voluntary effort that seeks to advance regional climate and Earth system science in Europe. As part of the World Climate Research Programme (WCRP) - Coordinated Regional Downscaling Experiment (CORDEX), it shares the broader goals of providing a model evaluation and climate projection framework and improving communication with both the General Circulation Model (GCM) and climate data user communities. EURO-CORDEX oversees the design and coordination of ongoing ensembles of regional climate projections of unprecedented size and resolution (0.11° EUR-11 and 0.44° EUR-44 domains). Additionally, the inclusion of empirical-statistical downscaling allows investigation of much larger multi-model ensembles. These complementary approaches provide a foundation for scientific studies within the climate research community and others. The value of the EURO-CORDEX ensemble is shown via numerous peer-reviewed studies and its use in the development of climate services. Evaluations of the EUR-44 and EUR-11 ensembles also show the benefits of higher resolution. However, significant challenges remain. To further advance scientific understanding, two flagship pilot studies (FPS) were initiated. The first investigates local-regional phenomena at convection-permitting scales over central Europe and the Mediterranean in collaboration with the Med-CORDEX community. The second investigates the impacts of land cover changes on European climate across spatial and temporal scales. Over the coming years, the EURO-CORDEX community looks forward to closer collaboration with other communities, new advances, supporting international initiatives such as the IPCC reports, and continuing to provide the basis for research on regional climate impacts and adaptation in Europe.

Added value of the regionally coupled model ROM in the East Asian summer monsoon modeling - Shoupeng Zhu; Armelle Reca C. Remedio; Dmitry V. Sein; Frank Sielmann; Fei Ge; Jingwei Xu; Ting Peng; Daniela Jacob; Klaus Fraedrich; Xiefei Zhi (Theoretical and Applied Climatology, 2020)

Effects of vineyard inter-row management on the diversity and abundance of plants and surface-dwelling invertebrates in Central Romania - Cristina Fiera; Werner Ulrich; Daniela Popescu; Claudiu-Ioan Bunea; Minodora Manu; Ioana Nae; Melania Stan; Bálint Markó; István Urák; Andrei Giurginca; Nicole Penke; Silvia Winter; et al. (Journal of Insect Conservation, 2020)
Vineyard inter-rows are important biodiversity hotspots within agricultural landscapes, especially when they are covered with vegetation. However, little is known on the effects to management intensity on a broad range of surface-dwelling invertebrates and their interaction with vegetation. We assessed the diversity and activity density of ants, beetles, millipedes, mites, spiders, springtails and woodlice using pitfall traps in vineyards with either high management intensity (HI) consisting of frequently tilled inter-rows or low management intensity (LO) with alternating tillage in every second inter-row. The study was performed in the Târnave wine region in Central Romania. We wanted to know whether, (i) vineyard management intensity affects the diversity of plants and invertebrates, and (ii) local habitat characteristics affect species richness of different functional guilds and taxa. Species richness of some invertebrate taxa (Coleoptera, Araneae, Formicidae) did significantly differ between HI and LO vineyards. Only phytophages (some Coleoptera) increased in species richness and activity density with vegetation cover. Vineyard soil properties (organic matter content, pH, P, and K) did not significantly differ between HI and LO vineyards. We conclude that vineyard inter-row management can affect both the conservation of biodiversity and the provision of biodiversity-driven ecosystem services.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

1.5°, 2°, and 3° global warming: visualizing European regions affected by multiple changes - Susanne Pfeifer; Diana Rechid; Maximilian Reuter; Elisabeth Viktor; Daniela Jacob (Regional Environmental Change, 2019)

Downstream effect of Hengduan Mountains on East China in the REMO regional climate model - Jingwei Xu; Nikolay V. Koldunov; Armelle Reca C. Remedio; Dmitry V. Sein; Diana Rechid; Xiefei Zhi; Xi Jiang; Min Xu; Xiuhua Zhu; Klaus Fraedrich; Daniela Jacob (Theoretical and Applied Climatology, 2019)

Does Regional Development Influence Sedimentary Blue Carbon Stocks? A Case Study From Three Australian Estuaries - Stephen Conrad; Dylan R. Brown; Paula Gomez Alvarez; Bronte Bates; Nizam Ibrahim; Alex Reid; Luciana Silva Monteiro; Daniela A. Silva; Lea T. Mamo; Jacob R. Bowtell; Huang An Lin; Nathaniel L. Tolentino; et al. (Frontiers in Marine Science, 2019)

On the role of horizontal resolution over the Tibetan Plateau in the REMO regional climate model - Jingwei Xu; Nikolay Koldunov; Armelle Reca C. Remedio; Dmitry V. Sein; Xiefei Zhi; Xi Jiang; Min Xu; Xiuhua Zhu; Klaus Fraedrich; Daniela Jacob (Climate Dynamics, 2018)

Sensitivity of the atmospheric water cycle to corrections of the sea surface temperature bias over southern Africa in a regional climate model - Torsten Weber; Andreas Haensler; Daniela Jacob (Climate Dynamics, 2018)

Revisiting an arid LGM using fluvial archives: a luminescence chronology for palaeochannels of the Murrumbidgee River, south‐eastern Australia - Daniela Mueller; Zenobia Jacobs; Tim J. Cohen; David M. Price; Ivars V. Reinfelds; James Shulmeister (Journal of Quaternary Science, 2018)
The Riverine Plain in south‐eastern Australia contains numerous palaeochannels that are much larger than the present rivers and provide evidence about past hydrological conditions. Previous research suggested optima in fluvial activity both before and after the peak of the Last Glacial Maximum (LGM; 21 ± 3 ka), and, in some cases, throughout the LGM. In this study, we revisit palaeochannel remnants of the Gum Creek and Yanco palaeochannel systems along the Murrumbidgee River, which drains the high‐elevation catchments of the Australian Alps in south‐eastern Australia. We date fluvial and aeolian sediments using single‐grain optically stimulated luminescence (OSL) and apply thermoluminescence (TL) dating to a subset of samples. We compare the OSL ages to new and previously published TL ages and investigate reasons for age discrepancies between these methods, possible effects of partial bleaching and other factors that may affect luminescence ages. We propose a new OSL‐based chronology for the Gum Creek and Yanco palaeochannel systems and assign periods of enhanced fluvial activity for the Tombullen and Yanco phases to 41–29 and 29–18 ka, respectively. Importantly, we infer that conditions of increased sediment and water discharge persisted for the Murrumbidgee River at the time of the LGM.

The South Atlantic Anticyclone as a key player for the representation of the tropical Atlantic climate in coupled climate models - William Cabos; Dmitry V. Sein; Joaquim G. Pinto; Andreas H. Fink; Nikolay V. Koldunov; Francisco Alvarez; Alfredo Izquierdo; Noel Keenlyside; Daniela Jacob (Climate Dynamics, 2017)

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

Development and validation of a coupled model system in the Baltic region—BALTIMOS - Daniela Jacob (Theoretical and Applied Climatology, 2014)

BALTIMOS—a coupled modelling system for the Baltic Sea and its drainage basin - Philip Lorenz; Daniela Jacob (Theoretical and Applied Climatology, 2014)

A comparison of the BALTIMOS coupled climate model with atmospheric and sea surface parameters derived from AMSR-E - Ralf Bennartz; Philip Lorenz; Daniela Jacob (Theoretical and Applied Climatology, 2014)

The surface radiation budget over South America in a set of regional climate models from the CLARIS-LPB project - Natalia L. Pessacg; Silvina A. Solman; Patrick Samuelsson; Enrique Sanchez; José Marengo; Laurent Li; Armelle Reca C. Remedio; Rosmeri P. da Rocha; Caroline Mourão; Daniela Jacob (Climate Dynamics, 2014)

Erratum to: EURO-CORDEX: new high-resolution climate change projections for European impact research - Daniela Jacob; Juliane Petersen; Bastian Eggert; Antoinette Alias; Ole Bøssing Christensen; Laurens M. Bouwer; Alain Braun; Augustin Colette; Michel Déqué; Goran Georgievski; Elena Georgopoulou; Andreas Gobiet; et al. (Regional Environmental Change, 2014)

EURO-CORDEX: new high-resolution climate change projections for European impact research - Daniela Jacob; Juliane Petersen; Bastian Eggert; Antoinette Alias; Ole Bøssing Christensen; Laurens M. Bouwer; Alain Braun; Augustin Colette; Michel Déqué; Goran Georgievski; Elena Georgopoulou; Andreas Gobiet; et al. (Regional Environmental Change, 2014)

Impact of modified soil thermal characteristic on the simulated monsoon climate over south Asia - Pankaj Kumar; Ralf Podzun**; Stefan Hagemann; Daniela Jacob (Journal of Earth System Science, 2014)

Assessing the robustness of projected precipitation changes over central Africa on the basis of a multitude of global and regional climate projections - Andreas Haensler; Fahad Saeed; Daniela Jacob (Climatic Change, 2013)

The simulation of European heat waves from an ensemble of regional climate models within the EURO-CORDEX project - Robert Vautard; Andreas Gobiet; Daniela Jacob; Michal Belda; Augustin Colette; Michel Déqué; Jesús Fernández; Markel García-Díez; Klaus Goergen; Ivan Güttler; Tomáš Halenka; Theodore Karacostas; et al. (Climate Dynamics, 2013)

Variability of extreme events in the Colombian Pacific and Caribbean catchment basins - Isabel Hoyos; Astrid Baquero-Bernal; Daniela Jacob; Boris A. Rodríguez (Climate Dynamics, 2013)

Influence of mid-latitude circulation on upper Indus basin precipitation: the explicit role of irrigation - Fahad Saeed; Stefan Hagemann; Sajjad Saeed; Daniela Jacob (Climate Dynamics, 2013)

A framework for the evaluation of the South Asian summer monsoon in a regional climate model applied to REMO - Fahad Saeed; Stefan Hagemann; Daniela Jacob (International Journal of Climatology, 2012)
Considering the complex spatial and vertical structure of the South Asian summer monsoon (SASM), the validation of a regional climate model (RCM) dealing with only a few surface variables is considered insufficient. Therefore, we have proposed an evaluation framework for the better assessment of the capability of an RCM in capturing the fundamental structure of SASM. This framework has been applied to the regional climate model REMO using ERA40 lateral boundary conditions for the period 1961–2000. The application of framework yielded satisfactory performance of REMO in capturing the lower, middle, and upper component of the SASM circulation. REMO has higher correlation between different SASM indices as compared to ERA40, showing its ability in capturing the dynamical link between these indices better than ERA40. We have employed different criteria for the assessment of the monsoon onset, and the movement of the Intertropical Convergence Zone (ITCZ) during the boreal summer and REMO has captured these phenomena reasonably well. The model has also shown the association of the meridional temperature gradient with the easterly shear of zonal winds. These results lead us to the conclusion that REMO is well suited for long‐term climate change simulations to examine projected future changes in the complex SASM system. Copyright © 2011 Royal Meteorological Society

The role of the simulation setup in a long-term high-resolution climate change projection for the southern African region - Andreas Haensler; Stefan Hagemann; Daniela Jacob (Theoretical and Applied Climatology, 2011)

Circumglobal wave train and the summer monsoon over northwestern India and Pakistan: the explicit role of the surface heat low - Sajjad Saeed; Wolfgang A. Müller; Stefan Hagemann; Daniela Jacob (Climate Dynamics, 2011)

Error characteristics of high resolution regional climate models over the Alpine area - Martin Suklitsch; Andreas Gobiet; Heimo Truhetz; Nauman Khurshid Awan; Holger Göttel; Daniela Jacob (Climate Dynamics, 2011)

Severe climate-induced water shortage and extremes in Crete - Ioannis K. Tsanis; Aristeidis G. Koutroulis; Ioannis N. Daliakopoulos; Daniela Jacob (Climatic Change, 2011)

Representing glaciers in a regional climate model - Sven Kotlarski; Daniela Jacob; Ralf Podzun; Frank Paul (Climate Dynamics, 2010)

Improved regional scale processes reflected in projected hydrological changes over large European catchments - Stefan Hagemann; Holger Göttel; Daniela Jacob; Philip Lorenz; Erich Roeckner (Climate Dynamics, 2009)

A high-resolution 43-year atmospheric hindcast for South America generated with the MPI regional model - Gabriel Silvestri; Carolina Vera; Daniela Jacob; Susanne Pfeifer; Claas Teichmann (Climate Dynamics, 2009)

Parameterization of snow-free land surface albedo as a function of vegetation phenology based on MODIS data and applied in climate modelling - Diana Rechid; Thomas J. Raddatz; Daniela Jacob (Theoretical and Applied Climatology, 2009)

Sensitivity of an ecosystem model to hydrology and temperature - Annett Wolf; Eleanor Blyth; Richard Harding; Daniela Jacob; Elke Keup-Thiel; Holger Goettel; Terry Callaghan (Climatic Change, 2008)

Influence of changed vegetations fields on regional climate simulations in the Barents Sea Region - Holger Göttel; Jörn Alexander; Elke Keup-Thiel; Diana Rechid; Stefan Hagemann; Tanja Blome; Annett Wolf; Daniela Jacob (Climatic Change, 2008)

Gradient in the climate change signal of European discharge predicted by a multi-model ensemble - Stefan Hagemann; Daniela Jacob (Climatic Change, 2007)

Modelling daily temperature extremes: recent climate and future changes over Europe - Erik Kjellström; Lars Bärring; Daniela Jacob; Richard Jones; Geert Lenderink; Christoph Schär (Climatic Change, 2007)

An inter-comparison of regional climate models for Europe: model performance in present-day climate - Daniela Jacob; Lars Bärring; Ole Bøssing Christensen; Jens Hesselbjerg Christensen; Manuel de Castro; Michel Déqué; Filippo Giorgi; Stefan Hagemann; Martin Hirschi; Richard Jones; Erik Kjellström; Geert Lenderink; et al. (Climatic Change, 2007)

Plant-specific promoter sequences carry elements that are recognised by the eubacterial transcription machinery - Daniela Jacob; Astrid Lewin; Beate Meister; Bernd Appel (Transgenic Research, 2002)

Gene Expression in Bacteria Directed by Plant-specific Regulatory Sequences - Astrid Lewin; Daniela Jacob; Barbara Freytag; Bernd Appel (Transgenic Research, 1998)